Transformasi Penyaluran Kredit Modal Kerja UMKM melalui Dana Pihak Ketiga: Kajian Sebelum dan Setelah Penerapan Keuangan Inklusif - Simangunsong, Bernadeth Yosephine Priskilla; Tri Darmawanto, Agus; Amin, Sinta Amin (Universitas Islam Negeri Raden Intan Lampung, 2025)
Banking financial institutions are integral components of the financial system, functioning as financial intermediaries that facilitate the flow of funds. The observed increase in third-party funds is attributed to the initiation of the Financial Inclusion Program. Currently, the banking sector is beginning to recognize the strategic importance of Micro, Small, and Medium Enterprises (MSMEs), especially considering their role as economic stabilizers during times of crisis. The primary objective of this study is to examine the effect of third-party funds on working capital loans for MSMEs, and to compare the outcomes before and after the implementation of financial inclusion policies. The study employs simple linear regression analysis alongside a paired t-test and descriptive analysis to assess the extent of implementation in the city of Tarakan. The findings reveal that third-party funds have a positive and significant influence on MSME working capital loans. Furthermore, significant differences are observed in both third-party funds and MSME working capital loans between the pre- and post-financial inclusion periods. The financial inclusion agents who participated in this study are all individual agents operating independently. In terms of service usage, the most frequent transactions reported by customers include fund transfers, bill payments, and cash withdrawals. However, these agents were also found to have limited financial literacy, indicating a gap in their understanding of broader financial concepts and practices.